Evaluation of the Performance of the Health Care Workers in Giving Consultation about the Fertility Promotion - Raziyeh Rahmati; talat khadivzadeh; Habiballah Esmaily; Hamid Reza Bahrami (Mashhad University of Medical Sciences, 2017)
Background & aim: Counseling is the first and most important tasks of the health care providers. The aim of this study was to evaluate the performance of the midwives and health care providers in the healthcare centers affiliated to the Mashhad University of Medical Sciences in giving consultation about the fertility promotion. Methods: This cross-sectional study was conducted on 107 midwives and health care providers working in the midwifery, maternal-child, and family planning units of the health centers and community health centers in Mashhad, Iran in 2015. The subjects of the study were selected using the stratified and cluster sampling methods. The data collection was performed using an observation checklist and a self-assessment questionnaire. The data were analyzed using the descriptive statistics, independent t-test, one-way ANOVA, Chi-square test, and Pearson correlation coefficient through the SPSS version 16. Results: According to the results of the study, the mean performance of the health workers in fertility counseling was 21.2±12.5 out of 79, which represented a weak level in this regard. The counseling performance had a significant relationship with the education, age of marriage, and husband's job (P